Novel pharmaceutical dosage forms of analgesics - Đekić Ljiljana; Primorac Marija (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
Among novel pharmaceutical dosage forms of analgesics, whose number and diversity are continuously increasing over the past two decades, of particular importance are transdermal opioid analgesics (fentanyl, buprenorphine) for the treatment of chronic pain, fentanyl iontophoretic transdermal drug delivery system for suppression of acute postoperative pain, as well as compressed lozenges, buccal tablets and film, sublingual tablets and nasal sprays for fentanyl treatment of breakthrough cancer pain. To improve the efficacy of the migraine pain treatment, compared to the solid dosage forms (tablets) of tryptans, pharmaceutical preparations of sumatriptan (solution for subcutaneous injection, nasal spray and nasal powder) and zolmitriptan (orodispersible tablet) are developed and marketed for migraine pain treatment. The benefits of these pharmaceutical preparations are minimal invasiveness and suitability to meet the individual therapeutic needs of patients, including the pediatric population, in terms of onset and duration of action and delivered dose of the drug. In the last few years, the European Medicines Agency (EMA) and the Food and Drug Administration (FDA) have warned of fatal errors during use or abuse of fentanyl transdermal patches and have indicated the importance educating health workers and patients about potential risks. Also, novel pharmaceutical forms of fentanyl for treatment of acute pain can be prescribed and used exclusively within the framework of the FDA REMS (Risk Evaluation and Mitigation Strategy) program aimed to provide greater benefits from potential risks. There are still no precise attitudes about the importance of recently approved pharmaceutical products of analgesics, and clinical assessments of their relative efficacy and tolerance at the site of application are also needed.